Serious Game for Immersion in Embedded Software Development: An Approach Focusing on Smart Homes - Santos, Cleidiana Reis dos; Seabra, Rodrigo Duarte (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2024)
The serious game proposed aims to provide an overview of some problems and solutions in embedded software development for smart homes. The game seeks to spark students’ interest in the subject, spreading the idea and motivating them to work in the development area. The game was implemented according to the Learning Mechanics – Game Mechanics (LM-GM) specification model. In order to investigate the educational impact provided by the experience of using the game, besides the questionnaires on usage and technical knowledge, the MEEGA+ questionnaire was used to evaluate the game. The results allow concluding that the game was able to introduce students to the Internet of Things area and motivate them to further their knowledge on the subject. The evaluation of the game by the students presented a positive overall result, as well as approval in seven of the eight dimensions used in the analysis.